2008
DOI: 10.1007/s00394-008-0720-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of clinical characteristics and dietary habits on the relationship between education status and 5-year incidence of cardiovascular disease: the ATTICA study

Abstract: Low education seems to increase CVD risk, an observation that was partially explained by baseline clinical characteristics and unhealthy dietary choices of people belonging into this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Educational status and CVD Panagiotakos et al (2008) showed that, in a Greek population, low education levels increased CVD risk, a finding partially explained by baseline clinical characteristics. In the Minnesota Heart Survey, it was shown that overall CHD risk was strongly related to educational level, the 10-year CHD mortality being highest in the least educated group (Luepker et al 1993).…”
Section: Educational Status and Cvd Risk Factorsmentioning
confidence: 91%
See 1 more Smart Citation
“…Educational status and CVD Panagiotakos et al (2008) showed that, in a Greek population, low education levels increased CVD risk, a finding partially explained by baseline clinical characteristics. In the Minnesota Heart Survey, it was shown that overall CHD risk was strongly related to educational level, the 10-year CHD mortality being highest in the least educated group (Luepker et al 1993).…”
Section: Educational Status and Cvd Risk Factorsmentioning
confidence: 91%
“…On the other hand, some studies demonstrate that education may have a protective effect against clinical disease through factors influencing overt disease, such as paying attention to symptoms, care-seeking behavior and adherence to medical treatment (Yan et al 2006). Furthermore, education is the best component of SES because it is reliable and valid and can be acquired, independent of occupation or age (Panagiotakos et al 2008), and it is also more strongly associated with CHD risk factors than the other socioeconomic components (Leino et al 1999;Winkleby et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The results from the studies either showed no relationship (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) or an inverse association (24)(25)(26)(27)(28)(29) between dairy product intake and risk of CVD and stroke.…”
Section: Milk and Total Dairy Product Intake And Cvd Risk: Evidence Fmentioning
confidence: 96%
“…Our previous study revealed an inverse association between educational attainment and some CVD risk factors such as lipid profile, blood pressure, and overweight, whereas no significant association was documented between smoking and educational level (Roohafza et al 2005). Many studies have shown that low education is positively associated with CVD risk factors (Panagiotakos et al 2008;Malyutina et al 2004;Pearson 2003). Occupation is one of the SES factors which is found to affect CVD risk factors independently (Gregory et al 2007;Helmert et al 1997).…”
Section: Introductionmentioning
confidence: 99%